Effect of Mode of Delivery and Number of Parity on Abnormal Placental Location - Shams, Mehwish Ara; Amin, Nabila; Syed, Humna (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the effect of mode of delivery and number of parity on abnormal placental location encountered at Pak Emirates Military Hospital Rawalpindi.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Gynaecology & Obstetrics, Pak Emirates Military Hospital Rawalpindi, from Jun 2019 to May 2020.Methodology: The study included all the antenatal patients with any abnormally placed placenta on ultrasound or MRI, if required, at the 32nd week of gestation. On ultrasound examination, controls were an equal number of antenatal women with the customarily located placenta. Factors like age, parity, previous mode of delivery, and iron deficiency anaemia were compared in both groups.Results: The mean age of the study participants was 32.11 ± 8.29 years. Out of 70 cases of abnormal placental location in pregnant women, 40 (57.1%) had placenta previa, 20 (28.6%) had accreta, while 10 (14.3%) had placenta percreta. Pearson chisquare test revealed that multiparity and previous deliveries by caesarean section had a statistically significant relationship with abnormal placental location among the study participants (p-value